Anisotropy of Full and Partial Anhysteretic Remanence Across Different Rock Types: 2—Coercivity Dependence of Remanence Anisotropy. Issue 2 (20th February 2020) - Biedermann, Andrea R.; Jackson, Mike; Bilardello, Dario; Feinberg, Joshua M.
Abstract: Magnetic fabrics are powerful tools in structural geology and tectonic studies, because they provide a fast and efficient measurement of mineral alignment, which helps interpret a rock's (de)formation history. The magnetic fabric of remanence‐carrying minerals provides useful information when these grains record different deformation stages than the bulk minerals in a rock. When rocks contain several subpopulations of remanence‐carrying minerals, each of these potentially displays a distinct fabric. This can lead to complex remanence anisotropies, being a superposition of all subpopulations' individual anisotropies. Characterization of partial remanence anisotropies has been used to investigate changes in fabric with grain size. However, most studies still report one bulk remanence anisotropy tensor per sample, and it remains to be determined how commonly different populations of remanence‐carrying grains reflect different subfabrics. Based on a large sample collection including 93 specimens from different lithologies, we have investigated the coercivity dependence of anisotropy of (partial) anhysteretic remanent magnetization A(p)ARM. We find that the principal directions, degree, and shape of A(p)ARM are generally dependent on the coercivity window used to impart the anhysteretic remanent magnetizations (ARMs). Depending on the carrier minerals and their fabrics, ARM anisotropy can either increase or decrease when the ARMs are applied over larger coercivity windows. Additionally, the coercivity fraction that dominates the ARM anisotropy is not always the coercivity fraction that acquires the strongest mean ARM. This illustrates the complexity of characterizing remanence anisotropy, and highlights the importance of carefully choosing experimental parameters in A(p)ARM determination for both magnetic fabric and anisotropy correction studies. Key Points: A(p)ARM tensors, principal directions, and anisotropy parameters depend on coercivity Fabrics of grain subpopulations can interfere positively or negatively Carefully choose and report experimental parameters for AARM determination